2002
DOI: 10.1101/lm.50102
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Interference in Sequence Learning and Prism Adaptation Inconsistent With the Consolidation Hypothesis

Abstract: The studies reported here used an interference paradigm to determine whether a long-term consolidation process (i.e., one lasting from several hours to days) occurs in the learning of two implicit motor skills, learning of a movement sequence and learning of a visuo-motor mapping. Subjects learned one skill and were tested on that skill 48 h later. Between the learning session and test session, some subjects trained on a second skill. The amount of time between the learning of the two skills varied for differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
102
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 48 publications
(48 reference statements)
8
102
1
Order By: Relevance
“…It is not a universal finding (Aberg and Herzog, 2010), and in studies that did report interference, it was found for widely varying time intervals, from 0 h up to 4 h in some studies (Brashers-Krug et al, 1996;Shadmehr and Holcomb, 1997;Seitz et al, 2005), to 24 h up to a week in others (Goedert and Willingham, 2002;Caithness et al, 2004;Zhang et al, 2008). These findings raise fundamental questions about the notion of time-limited consolidation and its relation to behavioral interference.…”
Section: Introductionmentioning
confidence: 63%
“…It is not a universal finding (Aberg and Herzog, 2010), and in studies that did report interference, it was found for widely varying time intervals, from 0 h up to 4 h in some studies (Brashers-Krug et al, 1996;Shadmehr and Holcomb, 1997;Seitz et al, 2005), to 24 h up to a week in others (Goedert and Willingham, 2002;Caithness et al, 2004;Zhang et al, 2008). These findings raise fundamental questions about the notion of time-limited consolidation and its relation to behavioral interference.…”
Section: Introductionmentioning
confidence: 63%
“…Consistent with this notion, individuals in the present investigation maintained the initial configurations of objects despite it being more effortful for task execution. In addition, the strength of association between a given context and action can also influence habit formation (e.g., Goedert & Willingham, 2013) and, in Experiments 1a and 1b, the more individuals had used a given configuration prior to the the final block. Lastly, past experiments have shown that a formally learned context-action coupling can inhibit the formation of subsequent ones (Wood & Neal, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…During this interval, there is no further practice, or even mention, of the procedure, and learning remains largely tacit or implicit (Brown & Robertson, 2007;Hallgato, Gyori-Dani, Pekar, Janacsek, & Nemeth, 2013;Krakauer & Shadmehr, 2006;Németh et al, 2010). Consolidation is also sometimes referred to as resistance to interference and forgetting (Ghilardi, Moisello, Silvestri, Ghez, & Krakauer, 2009;Goedert & Willingham, 2002;Stephan, Meier, Orosz, Cattapan-Ludewig, & KaelinLang, 2009). In the present study, we use the first definition (i.e., further improvement or enhancement).…”
Section: Introductionmentioning
confidence: 99%
“…We tested whether consolidation would OFFLINE CONSOLIDATION 7 differ for the learning of probabilistic and deterministic sequences, in particular, whether it might be stronger for deterministic sequences (see Deroost, Zeeuws, & Soetens, 2006;Destrebecqz & Cleeremans, 2001;Wilkinson & Jahanshahi, 2007). In fact, it has been shown that when sequence structure is complex, as it is for probabilistic sequences, offline consolidation of sequence learning may not occur (Goedert & Willingham, 2002), or at least not unless the sequence is explicit and not without an interval including sleep (see Cohen & Robertson, 2007;Song, 2009). …”
Section: Introductionmentioning
confidence: 99%